Integrating Green Marine Technology into Maritime Education in Indonesia - Titis Ari Wibowo; Jarot Delta Susanto; Setyawan Ajie Sukarno (International Journal of Marine Engineering Innovation and Research, 2026)
Indonesia’s maritime sector faces rising pressure to decarbonize ships and ports while maintaining safety and competitiveness. This paper examines how green marine technologies can be embedded into maritime vocational education so graduates are ready for shipboard and port-side sustainability initiatives (energy efficiency, emissions reduction, waste management, and alternative energy systems). An exploratory mixed-method design was used: semi-structured interviews with nine stakeholders (industry practitioners, maritime educators, and recent graduates) were complemented by a simple stakeholder rating instrument to assess curriculum integration, sustainability awareness, and industry relevance. Thematic analysis identified recurring needs and implementation constraints, while the ratings helped prioritize actions. Findings indicate that sustainability topics are present but unevenly distributed across courses and often lack measurable competency targets. Project-based learning and case studies were perceived as the most effective approaches, especially when supported by simulator/lab facilities and industry co-teaching. The strongest gap lies in translating regulations and green-technology concepts into practical marine-engineering tasks and assessment rubrics. The paper proposes priority actions for curriculum owners: competency mapping to green shipping operations, structured industry feedback loops, and incremental upgrading of learning infrastructure. These steps can strengthen graduate employability and accelerate sustainable practice adoption in the maritime industry.